Development of an Integrated Application to Improve Mini Bank Services at T. Amir Hamzah Indrapura Private Vocational School - Sinuraya, Junus; Sri A.B, Wiwin; Azanuddin; Purba, Bister (Cattleya Darmaya Fortuna, 2023)
Teaching Factory Mini Bank is a banking service that is limited in nature and focuses more on basic banking services, especially on a smaller financial scale in the school environment, especially T Amir Hamzah Indrapura Private Vocational School. The function of the mini bank in the T Amir Hamzah Private Vocational School school environment is to build financial independence in the school environment, facilitate financial transactions between students, student guardians, schools and banks as well as serving savings activities (financial inclusion) within the school environment, the general public around the school and as a media medium. learning financial services through direct practice. The aim of this research is to produce a prototype for developing an enterprise architecture that suits the needs of the Mini Bank SMKS T.Amir Hamzah Indrapura application system so that it can provide control direction in the development of a sustainable application system in accordance with the desired needs. The methodology in this research uses the Enterprise Architecture Planning (EAP) method which defines two rows and three columns from the Zachman framework. The results of this research produced a prototype for the development direction of applying enterprise architecture technology to improve the services of Mini Private Bank T Amir Hamzah Indrapura.